Laboratory Evidence on the Effects of Sponsorship on the Competitive Preferences of Men and Women - Baldiga, Nancy R.; Coffman, Katherine B. (Management Science, 2018)
Sponsorship programs have been proposed as one way to promote female advancement in competitive career fields. A sponsor is someone who advocates for a protégé, and in doing so, takes a stake in her success. We use a laboratory experiment to explore two channels through which sponsorship has been posited to increase advancement in a competitive workplace. In our setting, being sponsored provides a vote of confidence and/or creates a link between the protégé’s and sponsor’s payoffs. We find that both features of sponsorship significantly increase willingness to compete among men on average, while neither of these channels significantly increases willingness to compete among women on average. As a result, sponsorship does not close the gender gap in competitiveness or earnings. We discuss how these insights from the laboratory could help to inform the design of sponsorship programs in the field. Data, as supplemental material, are available at https://doi.org/10.1287/mnsc.2016.2606 . This paper was accepted by Uri Gneezy, behavioral economics.